KUA Sebagai Lembaga Bimbingan dan Konsultasi Pernikahan: Studi di KUA Kecamatan Medan Tembung Jalan Kapten Jamil - Nasution, Dwi Rizki Nabila; Abdul Bais; Khairil Andrean; Ahmad Yudha Ritonga; Mhd Rizky Rialdi Siregar; Hamka Ghozali (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The Office of Religious Affairs (KUA) plays a crucial role in guiding prospective spouses to understand the legal, social, and psychological aspects of marriage. This study aims to analyze the role of the KUA in Medan Tembung in providing premarital guidance and consultation services. The research uses a qualitative approach with interview techniques, observations, and document analysis. The findings indicate that KUA is not only an institution for marriage registration but also an entity that educates prospective spouses to build a harmonious family. The main challenge faced is the low awareness of the importance of premarital guidance. Therefore, innovative strategies are needed to increase community participation in marriage guidance programs.